Perancangan Konsep Taman Rekreasi Terpadu dan Pusat Penelitian Mangrove di Desa Pasar Rawa Langkat Menuju Ekosistem Mangrove Berkelanjutan - Erni Banjarnahor; Isnen Fitri (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Mangrove forests are essential for environmental protection, biodiversity conservation, and climate regulation. However, integrated mangrove ecotourism with research centres has not yet been moulded in Indonesia. Therefore, this study aims to propose a conceptual design for an Integrated Mangrove Recreation Park and Research Centre in Pasar Rawa Village, Langkat Regency, using a sustainable architectural and landscape approach. A mixed-method was applied through structured observations, in-depth interviews with tourism officials, tourism managers, and local communities, as well as SWOT analysis using EFAS and IFAS. Literature reviews and comparative studies preceded the research to determine design preferences. The design concept emphasises the integration of sustainability principles, including resource conservation, the utilisation of local materials, renewable energy sources, waste reduction, community empowerment, and multi-stakeholder collaboration. The findings indicate that facilities integrating mangrove conservation, environmental education, and sustainable recreation are highly needed. The design emphasises ecological harmony, community and stakeholder engagement, educational impact, and sustainable accessibility and operations to support mangrove ecosystems while ensuring the long-term success of tourism. This recreation park is expected not only to become a new tourist destination but also to serve as a model of integrated, inclusive, and sustainable edutourism and ecotourism with positive ecological, social, and economic impacts.